Big Tobacco, Alcohol, and Food and NCDs in LMICs: An Inconvenient Truth and Call to Action; Comment on "Addressing NCDs: Challenges From Industry Market Promotion and Interferences" - Peter Delobelle (Kerman University of Medical Sciences, 2019)
In their editorial, Tangcharoensathien et al1 describe the challenges of industry market promotion and policy interference from Big Tobacco, Alcohol, and Food in addressing non-communicable diseases (NCDs). They provide an overview of the increasing influence of corporate interest in emerging economies and government attempts to implement the World Health Organization (WHO) 'best buy' interventions. The authors largely draw on examples from Asia and a few selected countries, but provide little detail as to how aggressive marketing and policy interference plays out in a context of poor legislation and regulation in many low- and middleincome countries (LMICs), where the burden of NCDs is increasing at an alarming rate and governments face a high burden of disease with a limited budget for countering industry interference. This commentary provides some poignant examples of the influence of Big Tobacco, Alcohol, and Food on market regulation and policy interference in LMICs and argues for more policy coherence and accountability in terms of multisectoral action and civil society activism. Securing funds for health promotion and establishing health promotion foundations could help achieve that goal.